Protective Effects and Mechanisms of Polyethylene Glycol Loxenatide Against Hyperglycemia and Liver Injury in db/db diabetic Mice - Zhang, Yu; Li, Yufeng; Zhao, Junjun; Wang, Cong; Deng, Bin; Zhang, Qilin; Shi, Chen (Frontiers in Pharmacology, 2021)
Background: Type 2 diabetes mellitus (T2DM) is a metabolic disorder with insulin resistance and impaired insulin secretion that can cause complications, including liver injury. Polyethylene glycol loxenatide (PEG-Loxe), a glucagon-like peptide-1 (GLP-1) analog, is widely used to treat T2DM. However, its specific glucose-lowering and hepatoprotective mechanisms of action have not been established yet. METHODS: Using a high glucose-induced hepatocyte injury model and a type 2 diabetic db/db mouse model, we assessed PEG-Loxe’s impact on reducing blood glucose and improving liver injury in T2DM and revealed its mechanism. RESULTS: PEG-Loxe treatment significantly reduced body weight and fasting glucose, increased glucose tolerance, improved serum and liver biochemical parameters (glycated hemoglobin, serum insulin, triglycerides, total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, alanine aminotransferase, and aspartate aminotransferase), and attenuated hepatic steatosis and liver and pancreatic tissue damages in db/db mice. Additionally, PEG-Loxe considerably inhibited oxidative stress, decreased pro-inflammatory factor (TNF-α, IL-6, and MCP-1) levels, and increased anti-inflammatory factor IL-10 levels. PEG-Loxe possibly inhibits hepatic lipid synthesis, oxidative stress, and inflammatory response by upregulating Sirt1, p-AMPK, and p-ACC expressions in the Sirt1/AMPK/ACC pathway of lipid metabolism, thereby improving T2DM liver injury. PEG-Loxe most likely also promotes GLP-1R expression by inhibiting β-cell apoptosis, which in turn activates the insulin PI3K/AKT pathway to promote insulin synthesis and secretion, thereby exerting hypoglycemic effects. In vitro cellular experiments further confirmed that PEG-Loxe possibly exerts hypoglycemic effects by activating the insulin PI3K/AKT pathway. Conclusion: PEG-Loxe improved liver injury in T2DM probably by activating Sirt1/AMPK/ACC lipid metabolism pathway, and exerted hypoglycemic effects through activation of insulin PI3K/AKT pathway.